Polymeric spinal cage developed via ct-fea - Muhammad Hilmi, Jalil; Omar, Nadzeri; Muhd Hazli, Mazlan; Mahendran, Kugendran; Mohd Firdaus, Mak Nanyan (2021)
To treat back pain,PLIF procedure using cage is done. Main problem-stress shielding, no fea for prediction, of failure and High material cost